Effects of municipal smoke-free ordinances on secondhand smoke exposure in the Republic of Korea - Kim, Siwoo; Lee, Yuri; Han, Changwoo; Kim, Min Kyung; Kawachi, Ichiro; Oh, Juhwan (Frontiers in Public Health, 2023)
Objective: To reduce premature deaths due to secondhand smoke (SHS) exposure among non-smokers, the Republic of Korea (ROK) adopted changes to the National Health Promotion Act, which allowed local governments to enact municipal ordinances to strengthen their authority to designate smoke-free areas and levy penalty fines. In this study, we examined national trends in SHS exposure after the introduction of these municipal ordinances at the city level in 2010. Methods: We used interrupted time series analysis to assess whether the trends of SHS exposure in the workplace and at home, and the primary cigarette smoking rate changed following the policy adjustment in the national legislation in ROK. Population standardized data for selected variables were retrieved from a nationally representative survey dataset and used to study the policy action’s effectiveness. Results: Following the change in the legislation, SHS exposure in the workplace reversed course from an increasing (18% per year) trend prior to the introduction of these smoke-free ordinances to a decreasing (-10% per year) trend after adoption and enforcement of these laws (β2=0.18, P value=0.07; β3=-0.10, P value=0.02). SHS exposure at home (β2=0.10, P value=0.09; β3=-0.03, P value=0.14) and the primary cigarette smoking rate (β2=0.03, P value=0.10; β3=0.008, P value=0.15) showed no significant changes in the sampled period. Although analyses stratified by sex showed that the allowance of municipal ordinances resulted in reduced SHS exposure in the workplace for both males and females, they did not affect the primary cigarette smoking rate as much, especially among females. Conclusion: Strengthening the role of local governments by giving them the authority to enact and enforce penalties on SHS exposure violation helped ROK to reduce SHS exposure in the workplace. However, smoking behaviors and related activities seemed to shift to less restrictive areas such as on the streets and in apartment hallways, negating some of the effects due to these ordinances. Future studies should investigate how smoke-free policies beyond public places can further reduce the SHS exposure in ROK.